Journeys of the mind a life in history - Brown, Peter 1935- (Princeton University Press, 2023)
"An intellectual autobiography by Peter Brown, one of the most eminent historians of the last 50 years, who is credited with having created the field of study know as Late Antiquity, the period during which Rome fell, the three major monotheistic religions took shape, and Christianity spread across Europe situating it in the major developments in historiography and the study of the religion in the 20th century and the minds behind them."
Keywords: Brown, Peter -- 1935-; Altertumswissenschaft; Brown, Peter / 1935-; Historians / United States / Biography; BIOGRAPHY & AUTOBIOGRAPHY / General; RELIGION / Christianity / History; Autobiografie